Lower Cerebrovascular Reactivity Contributed to White Matter Hyperintensity‐Related Cognitive Impairment: A Resting‐State Functional MRI Study - Ni, Ling; Zhang, Bing; Yang, Dan; Qin, Ruomeng; Xu, Hengheng; Ma, Junyi; Shao, Pengfei; Xu, Yun (Journal of magnetic resonance imaging, 2021)
Background Impaired cerebrovascular reactivity (CVR) plays an important role in the pathophysiology of white matter hyperintensities (WMHs). The pathogenesis of CVR in the development of WMH‐related cognitive impairment (CI) remains poorly understood. Purpose To detect the CVR status in WMH subjects with/without CI by using a resting‐state blood oxygenation level‐dependent (BOLD) approach and to explore the mediating relationships among CVR, WMH, and cognitive level. Study Type Prospective. Subjects Subjects with moderate to severe WMH (with CI [WMH‐CI], n = 68; without CI [WMH‐no‐CI, n = 63) as well as normal controls (NCs, n = 87). Field Strength/Sequence 3.0T with gradient‐recalled echoplanar imaging and 3D fluid‐attenuated inversion recovery. Assessment The CVR, WMH volume, and cognitive level were assessed. The CVR map was derived using BOLD signal obtained from resting‐state functional MRI data. Statistical Tests CVR maps were compared among the three groups. Partial correlation analyses were performed to correlate impaired CVR with WMH volume and cognitive test scores. Mediation analysis was conducted to determine whether WMH acted as a mediating factor between CVR and cognitive function. Results Compared with the NC group, both WMH groups showed reduced CVR in the left hemisphere (P < 0.05). The WMH‐CI group showed further decreased CVR in the left frontal area, when compared with the WMH‐no‐CI group (P < 0.05). In the WMH‐CI group, the lower CVR in left frontal area was a strong indicator of poor performance on general cognition (r = 0.311), executive function (r = 0.362), and information processing speed (r = 0.399) (all P < 0.05). Periventricular WMH (PWMH) volume mediated these correlations, the β and 95% bootstrap confidence intervals were (0.5097, [0.1498,1.1385]), (−0.4081, [−1.0256,‐0.1363]), and (−0.5576, [−1.4666,‐0.1538]), respectively. Data Conclusion WMH‐CI subjects showed a greater reduction of CVR derived from a resting‐state BOLD approach in the left frontal area than WMH‐no‐CI subjects. Cognition was highly dependent on the integrity of cerebrovascular reactivity and mediated by PWMH burden. Level of Evidence 4 Technical Efficacy Stage 2